Application value of PET/CT in monophasic primary sacral synovial sarcoma: a case report and review of literature - Shao, Mingyan; Xu, Rong; Qi, Wanling; Luo, Zhehuang; Liao, Fengxiang; Fan, Sisi (Frontiers in Oncology, 2024)
Background:Synovial sarcoma is a malignant tumor of mesenchymal origin with high degree of malignancy and easy metastasis. It mostly occurs in distal extremities or adjacent joints, it is most common in deep knee joint.Primary sacral synovial sarcoma(PSSS) is extremely rare. The PET/CT imaging findings of a case of monophasic Primary sacral synovial sarcoma were reported. The clinical, imaging and pathological data were summarized, and the literature was reviewed. Case description:A 67-year-old female patient presented with sacrococcygeal pain without obvious causes on 2022-09-16, with occasional pain at night, aggravated pain during hip flexion and long distance walking, which could be slightly relieved with rest, without special treatment.For further treatment before 1 month to Jiangxi Provincial People's Hospital,After admission,laboratory tests were negative.Non-contrast CT scan (FIG.1) showed expansive bone destruction in the S1-3 vertebrae with soft tissue density of about 58*46*52mm. The boundary was clear, necrosis was visible within the vertebrae, and the boundary between the mass and the anterior sacral blood vessels and rectum was unclear.Non-contrast MRI scan (FIG.2) showed mixed signals in lumbosacral masses, with equal signals in T1 and uneven and slightly higher signals in T2. Cystic degeneration and necrosis were visible, with multiple compartments in the lumbosacral masses.MRI enhancement showed uneven enhancement of lumbosacral mass with multiple compartments and no enhanced cystic lesion.The left sacral alar bone is destroyed, as shown by large flaky uneven strengthening.PET/CT(FIG.3) showed that S1-3 vertebral body and left sacral alar bone were destroyed and soft tissue shadow formed, invading the sacral canal and the left foramina of S1-3. FDG metabolism was significantly increased, and malignant tumor was diagnosed by PET/CT. Pathological examination (FIG.4):The pathological diagnosis was monophasic Primary sacral synovial sarcoma.After systemic chemotherapy and local radiotherapy, no significant signs of recurrence and metastasis were found on CT so far.Follow-up treatment was continued. Conclusion:The incidence of primary sacral synovial sarcoma is very low, and its clinical and imaging manifestations lack characteristics, and the final diagnosis still needs pathology.PET/CT imaging has a certain value in the diagnosis of primary sacral synovial sarcoma, and has great application value in the preoperative staging, postoperative efficacy evaluation and follow-up.